Assessing the potential of augmented reality (AR) as attributes of successful learning of heritage architecture - Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah; Azmin, Aida Kesuma (2017)
The usage of Augmented Reality (AR) in architecture field is considered in an infant stage as compared to other disciplines such as medical science and entertainment. Thus, this research explores possibilities of using AR to enhancing architectural representation of heritage buildings. The objectives of the research are to identify potential and challenge of AR in enhancing architectural representation of heritage buildings in Malaysia; to explore the processes of producing architectural virtual modellings of 13 types of the Malay traditional houses, and their AR prototypes; and to recommend how implementation of AR could be used in teaching and learning architecture, specifically in relation to timber construction class and heritage architecture class. This research will be conducted using qualitative approach, with substance of exploratory action research. It is anticipated that this research will contribute in providing clear knowledge on the advancement of Augmented Reality in Architecture; regulating the ranges of process involved in the development and application of Augmented Reality (AR) in architecture; and recommending ranges of possibility of applying AR technology in Architectural learning. The findings of the research may implicate the ways advanced technology is used in architecture, to the extent that visualization of projects could be simulated in a clearer manner prior to construction.